Development and Validation of a Mathematical Model to Predict the Complexity of FMR1 Allele Combinations - Rodrigues, Bárbara; Vale-Fernandes, Emídio; Maia, Nuno; Santos, Flávia; Marques, Isabel; Santos, Rosário; Nogueira, António J. A.; Jorge, Paula (Frontiers in Genetics, 2020)
The polymorphic trinucleotide repetitive region in the FMR1 gene 5′UTR contains AGG interspersions, particularly in normal-sized alleles (CGG < 45). In this range repetitive stretches are typically interrupted once or twice, although alleles without or with three or more AGG interspersions can also be observed. AGG interspersions together with the total length of the repetitive region confer stability and hinder expansion to pathogenic ranges: either premutation (55 < CGG < 200) or full mutation (CGG > 200). The AGG interspersions have long been identified as one of the most important features of FMR1 repeat stability, being particularly important to determine expansion risk estimates in female premutation carriers. We sought to compute the combined AGG interspersion numbers and patterns, aiming to define FMR1 repetitive tract complexity combinations. A mathematical model, the first to compute this cumulative effect, was developed and validated using data from 131 young and healthy females. Plotting of their allelic complexity enabled the identification of two statistically distinct groups – equivalent and dissimilar allelic combinations. The outcome, a numerical parameter designated allelic score, depicts the repeat substructure of each allele, measuring the allelic complexity of the FMR1 gene including the AGGs burden, thus allowing new behavioral scrutiny of normal-sized alleles in females.